Gitelman syndrome and primary hyperparathyroidism: a rare association. (5th June 2018) - Rego, Teresa; Fonseca, Fernando; Cerqueira, Rita; Agapito, Ana
Abstract : Gitelman syndrome(GS) is a rare autosomal recessive salt-losing tubulopathy of young adults, characterised by hypokalaemia, hypomagnesaemia, hypocalciuria and secondary hyperaldosteronism. Hypercalcaemia due to hypocalciuria in these patients is extremely rare. A 25-year-old healthy woman was referred to the Endocrinology clinic for evaluation of persistent hypokalaemia. She presented with fatigue, myalgias, cramps and paraesthesia. Her physical examination was normal. Laboratory workup revealed: K + 2.7 mEq/L (r.v.3.5–5.1), 24 hours urinary K + 84.7 mEq/24 hours (r.v.25–125), Mg 2+ 0.71 mg/dL (r.v.1.6–2.6), 24 hours urinary Mg 2+ 143.1 mg/24 hours (r.v.73–122), Ca 2+ 12 mg/dL (r.v.8.4–10.2), aldosterone 47.1 ng/mL (r.v. 4–31) and active renin 374.7 uUI/mL (r.v.4.4–46.1). She was diagnosed with GS and was treated with spironolactone, oral K + and Mg 2+ supplementation. Further investigation confirmed hypercalcaemia due to primary hyperparathyroidism owing to a single parathyroid adenoma. Following parathyroidectomy serum calcium normalised. Current knowledge favours that hypomagnesaemia in patients with GS protects them from hypercalcaemia. In this context of multiple electrolyte imbalances, correction of hypomagnesaemia is a challenge and should be done carefully. Like in our patient, aetiology of hypercalcaemia should be promptly diagnosed and reversed.